The Effectiveness of Islamic Capital Market Schools in Enhancing Knowledge and Motivation towards Stock Investment in Generation Z - Hani Hasanah; Kurniawati, Ria (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
This research aims to determine the difference between before and after the implementation of the Shariah capital market school at Sheikh-Yusuf Islamic University Campus. This study is a quantitative research using the Mann-Whitney test as a differential test. Based on the research results, it is found that there is a difference in motivation and knowledge of the students at Sheikh-Yusuf Islamic University before and after the implementation of the Shariah capital market school activities.